Biophysical Evaluation of Caffeine Analogues as Multi-Targeted AntiAlzheimer’s Agents - Vietri, Agustin (2025)
The main objective of this study was to identify an analog capable of acting on multiple relevant targets in Alzheimer’s disease (AD), thereby achieving an integral treatment of this condition through a single molecule. To this end, we designed twenty-nine caffeine analogs aimed at enhancing cholinergic activity, modulating apoptosis and immunity, and promoting neuroprotection. We thoroughly analyzed the pharmacokinetic and molecular properties of each analog, performing molecular docking studies on fourteen targets (using virtual screening, blind docking, or both, depending on the target) to evaluate binding affinity. Pharmacokinetic parameters were predicted using Deep-PK and SwissADME, and molecular docking was performed using the Docthor online software. Validation of results were achieved by incorporating decoy molecules, positive controls, and ROC curve analyses. Among the candidates, analog T-49-I emerged as the most promising due to its strong multi-target affinity and favorable pharmacokinetic profile. However, we also identified other analogs that, despite less favorable pharmacokinetics, displayed selective affinity for specific targets or target groups relevant to particular therapeutic goals. Furthermore, we uncovered common molecular features that could guide the rational design of future analogs. This study provides qualitative structure– activity relationship insights that are valuable for developing multitarget molecules capable of simultaneously modulating various therapeutic targets in AD.